HyperChildNET COST Action CA19115: report of the task force - Lurbe, Empar; Mancia, G.; Drozdz, D.; Erdine, S.; Fernandez-Aranda, F.; Litwin, M.; Sinha, M. D.; Simonetti, G.; Stabouli, S.; Wühl, Elke (Blood pressure, 2024)
Purpose: Despite dramatic medical advances over the last few decades, cardiovascular disease remains a leading cause of death globally. High BP is clearly established, but modifiable, risk factor for early disability and death. Although most of the adverse outcomes occur in adulthood it has become clear that high BP is a life course problem that can become evident in early life however, relatively little attention has been paid to the problem of high BP in children and adolescents. Materials and methods: Being aware of the problem and the needs, the Task Force of the ESH Guidelines in children and adolescents took the initiative to move forward in the field, identifying the COST Action program. A proposal, HyperChildNET, was submitted, approved and funded for 4 years starting in October 2020. Results: The aim of the Action has been to establish a European sustainable and multidisciplinary network of researchers, clinicians, early career investigators, health economists, decision-makers, regulatory bodies, and medical devices manufacturers under the umbrella of the European Commission in order to acquire a holistic understanding of those factors affecting high BP in children and adolescents in order to propose and implement preventive and corrective actions. All the activities carried out during the 4 years are described. Conclusions: HyperChildNET offers a European perspective of the issue giving us the opportunity to develop new strategies and objectives moving forward in the field.
Gesehen am 13.08.2025